Reconciling differences in natural tags to infer demographic and genetic connectivity in marine fish populations - Reis-Santos, Patrick; Tanner, Susanne E.; Aboim, Maria Ana; Vasconcelos, Rita P.; Laroche, Jean; Charrier, Grégory; Perez, Montse; Presa, Pablo; Gillanders, Bronwyn M.; Cabral, Henrique (Scientific Reports, 2018)
WOS:000437830200039 International audience Processes regulating population connectivity are complex, ranging from extrinsic environmental factors to intrinsic individual based features, and are a major force shaping the persistence of fish species and population responses to harvesting and environmental change. Here we developed an integrated assessment of demographic and genetic connectivity of European flounder Platichthys flesus in the northeast Atlantic (from the Norwegian to the Portuguese coast) and Baltic Sea. Specifically, we used a Bayesian infinite mixture model to infer the most likely number of natal sources of individuals based on otolith near core chemical composition. Simultaneously, we characterised genetic connectivity via microsatellite DNA markers, and evaluated how the combined use of natural tags informed individual movement and long-term population exchange rates. Individual markers provided different insights on movement, with otolith chemistry delineating Norwegian and Baltic Sea sources, whilst genetic markers showed a latitudinal pattern which distinguished southern peripheral populations along the Iberian coast. Overall, the integrated use of natural tags resulted in outcomes that were not readily anticipated by individual movement or gene flow markers alone. Our ecological and evolutionary approach provided a synergistic view on connectivity, which will be paramount to align biological and management units and safeguard species' biocomplexity.